Pengaruh Edukasi Kesehatan Menggunakan Leaflet Terhadap Penurunan Dismenore Di SMPS Al-Manar Medan - Husna, Asy Syfah; Silaen, Harsudianto (Indonesian Trust Nursing Journal, 2025)
Dysmenorrhea causes limitations in women in carrying out daily activities, school absences,and social withdrawal, therefore appropriate treatment is needed, carried out to reduce theincidence of dysmenorrhea. Factors that can influence efforts to treat dysmenorrhea areknowledge. In this study, health education will be provided using leaflets. This study aimsto determine the effect of health education using leaflets on reducing dysmenorrhea. Thistype of research is quantitative which is a pre-experimental study with a one group pre-posttest design using a total sampling technique. The number of samples in this study was71 people. Students' knowledge of treating dysmenorrhea was measured using aquestionnaire. Data analysis of this study used the Wilcoxon test. Based on the results ofthe analysis obtained, there was a p-value of 0.001 (p  0.05) which showed that there wasa significant effect of education using leaflets on reducing dysmenorrhea. It isrecommended to conduct further research with more samples and add different variablessuch as the effect of dysmenorrhea gymnastics on reducing dysmenorrhea.